Changes in the fine-scale genetic structure of Finland through the 20th century - Kerminen, Sini; Cerioli, Nicola; Pacauskas, Darius; Havulinna, Aki S.; Perola, Markus; Jousilahti, Pekka; Salomaa, Veikko; Daly, Mark J.; Vyas, Rupesh; Ripatti, Samuli; Pirinen, Matti (PLOS Genetics, 2021)
Author summary We have inherited our genomes from our parents, who, in turn, inherited their genomes from their parents, etc. Hence, a comparison between genomes of present day individuals reveals genetic population structure due to the varying levels of genetic relatedness among the individuals. We have utilized over 18,000 Finnish samples to characterize the fine-scale genetic population structure in Finland starting from a binary East-West division and ending up with 10 Finnish source populations. Furthermore, we have applied the resulting ancestry information to generate records of how the population structure has evolved each year between 1923 and 1987 in 12 geographical regions of Finland. For example, the war-related evacuation of Karelians from Southeast Finland to other parts of the country show up as a clear, sudden increase in the Evacuated ancestry elsewhere in Finland between 1939 and 1945. Additionally, different regions of Finland show very different levels of genetic mixing in 1900s, from little mixed regions like Ostrobothnia to highly mixed regions like Southwestern Finland. To distribute the results among general public, we provide an interactive website for browsing the municipality and region-level genetic ancestry profiles at https://geneviz.aalto.fi/genetic_ancestry_finland/